Correlation between in silico and in vitro Results of 1-(Benzoyloxy)urea and its Derivatives as Potential Anti-Cancer Drugs - Suko Hardjono (Lviv Polytechnic National University, Lviv, Ukraine, 2017)
1-(Benzoyloxy)urea and its derivatives were synthesized by modified Scotten-Bauman reaction with adding benzoyl chloride or homologs to hydroxyurea in tetrahydrofuran. Structure characterization was conducted based on ultra-violet (UV-VIS) spectrum, infrared (FT-IR), H nucleus magnetic resonance (1H NMR), C nuclear magnetic resonance (13C NMR) and mass spectrometry (MS). In silico test to predict anti-cancer activity of 1-(benzoyloxy)urea and its derivatives in ribonucleotide reductase enzyme (PDB: 2EUD) was done using Molegro Program. The anti-cancer activity test was performed in vitroby using MTT method to HeLa cell lines. In silico test result (Rerank Score) was correlated relative to anti-cancer activity (log1/IC50). There was a significant linear relationship between in vitroand in silico anti-cancer activity.